As primeiras experiências do espírito que se diferencia de seu objeto: uma leitura sistemática das formas de consciência e autoconsciência na Fenomenologia do espírito, de Hegel - Martins, Maria Ivonilda da Silva (2012)
This inquiry, as the title indicates, intends to present a systematic reading of the consciouness and self-consciouness figures in Hegel’s Phenomenology of Spirit. I argue that we can not renounce experiences analysis in which the spirit manifests, because only through them we can realize how consciouness becomes able to acquire the knowledge of itself and content itself in a mode of self-understanding unified with itself: the spirit.